The influence of the fluid flow velocity and direction on the wave dispersion in the initially inhomogeneously stressed hollow cylinder containing this fluid - Akbarov, Surkay D.; Imamaliyeva, Jamila N.; Akbarli, Reyhan S. (TECHNO-PRESS, 2024)
The paper studies the influence of the fluid flow velocity and flow direction in the initial state on the dispersion of the axisymmetric waves propagating in the inhomogeneously pre -stressed hollow cylinder containing this fluid. The corresponding eigenvalue problem is formulated within the scope of the three-dimensional linearized theory of elastic waves in bodies with initial stresses, and with linearized Euler equations for the inviscid compressible fluid. The discrete -analytical solution method is employed, and analytical expressions of the sought values are derived from the solution to the corresponding field equations by employing the discrete -analytical method. The dispersion equation is obtained using these expressions and boundary and related compatibility conditions. Numerical results related to the action of the fluid flow velocity and flow direction on the influence of the inhomogeneous initial stresses on the dispersion curves in the zeroth and first modes are presented and discussed. As a result of the analyses of the numerical results, it is established how the fluid flow velocity and flow direction act on the magnitude of the influence of the initial inhomogeneous stresses on the wave propagation velocity in the cylinder containing the fluid.
Keywords: compressible inviscid fluid; fluid flow velocity; hydro-elastic system; inhomogeneous initial stresses; wave dispersion; AXISYMMETRICAL LONGITUDINAL-WAVES; LOADED CYLINDRICAL-SHELLS; VISCOUS-LIQUID LAYER; LAMB WAVES; PROPAGATION; SYSTEM; PRESTRESSES; Mechanics